Effect of washing aggregate sludge waste on the properties of alkali-activated blast furnace slag - Bilici, Senem; Kabay, Nihat; Miyan, Nausad; Omur, Tarik; Ozkan, Hakan (ELSEVIER, 2023)
The growing production of aggregates in quarries leads to the generation of solid wastes and an expansion of energy footprint. Since these solid wastes are generally stored in landfills, they cause environmental and economic problems. This paper sought to provide a sustainable alternative for the valorization processes of one of these solid wastes, washing aggregate sludge (WS) obtained from a specific aggregate quarry, by investigating the possibility of its utilization as a supple-mentary precursor material in alkali-activated paste and mortars. The mixtures were produced by replacing the blast furnace slag (BFS) with WS by 0, 25, 50, and 75 wt%, and the effect of WS on the physical, mechanical, durability, and microstructural properties of samples was comprehen-sively studied. The results revealed that the incorporation of WS consistently extended the setting time of mixes, providing a suitable setting time range for ease of handling, and the setting time of mixtures was predominantly influenced by the initial SiO2/Al2O3 molar ratio. The mechanical and physical test results indicated that the increase in WS replacement ratios increased the water absorption, voids content, drying shrinkage, and sorptivity values, and reduced the compressive strength of alkali-activated mortar samples. On the other hand, an increase in WS ratio efficiently increased the residual compressive strength values of mortar specimens during wetting-drying cycles, indicating its suitability for warm and moist climatic areas. The microstructure analysis revealed that C-A-S-H type gels were mainly formed in the reference mix (100% BFS), whereas N-A-S-H along with C-A-S-H type gels were detected in the specimens produced with a higher WS ratio. The incorporation of WS up to 25% to produce BFS-based AAM as a construction material can be a competent method to efficiently utilize WS waste which may also protect the environ-ment and ensure sustainability.
Keywords: Washing aggregate sludge; Alkali-activated mortar; Sorptivity; Wet-dry cycle; Microstructure; RICE HUSK ASH; FLY-ASH; DRYING SHRINKAGE; COMPRESSIVE STRENGTH; MICROSTRUCTURE CHARACTERISTICS; MECHANICAL-PROPERTIES; GEOPOLYMER CONCRETE; TEMPERATURE; WATER; PERMEABILITY; Construction & Building Technology; Engineering